Quilotórax: una presentación inusual de síndrome linfoproliferativo. - Aurea Lima; Diana Dias; Joana Malheiro; Joana Rodrigues (Sociedade Galega de Medicina Interna, 2021)
Chylothorax, accumulation of chylous fluid in the pleural space, may have traumatic, postoperative or malignant etiology. We report the case of a healthy 20-year-old woman referred to the emergency department for 2 months with progressive asthenia and dyspnea associated with left cervical pain not responsive to analgesia. On admission, sinus tachycardia, tachypnea, and auscultatory silence in the left hemithorax, without respiratory insufficiency, stand out. CXR revealed opacity of the left pulmonary hemicamp and contralateral deviation of the mediastinum (Figure 1). Analytically, with hypochromic microcytic anemia, increased lactate dehydrogenase (LDH) and C-reactive protein. Thoracocentesis with 1000mL draining of milky-looking pleural fluid analytically compatible with chylothorax (pH 7.5, 935 leukocytes/µL - 29% polymorphonuclear and frank predominance of proteins, 5.3g/dL, triglycerides 684mg/dL, cholesterol 123mg/dL, normal glucose and LDH, amicrobial). Thoracoabdominal-pelvic tomodensitometry detected a mediastinal solid mass, 78x94x121mm, lobulated contours and no cleavage planes with pericardial, aortic cross or thoracic operculum, with supraclavicular extension associated with left atelectasis. and pleural effusion in the left hemithorax with signs of compression and contralateral mediastinal deviation (Figure 2). On admission, the diagnosis of classic Hodgkin's lymphoma of the nodular sclerosis subtype (stage II-B) was established. Completed 6 cycles of chemotherapy with curative intent, with evidence of complete remission after 2nd cycle on positron emission tomography. The present image aims to explain the possible presentation of Hodgkin's Lymphoma: indolent presentation and without severe clinical repercussion of extensive pleural effusion and associated large mediastinal mass. Moreover, it reinforces the importance of differential diagnosis of pleural effusion, recalling chylothorax as the underlying cause.